New Insight in the Occurrence of Early Blight Disease on Potato Reveals High Distribution of Alternaria solani and Alternaria protenta in Serbia - Ivanović, Žarko; Blagojević, Jovana; Jovanović, Gordana; Ivanović, Borko; Žeželj, Danica (Frontiers in Microbiology, 2022)
Early blight is an economically important disease of potato worldwide. Understanding which fungal pathogens are the causal agents of early blight and their distribution on the same host is essential to finding the best strategy for the control of this disease. Previous studies have shown that Alternaria solani is the main early blight pathogen parasitizing potato. Here, we analyzed genetic and phenotypic diversity in isolates of Alternaria spp. covering all potato production areas in Serbia. We showed that the four species of Alternaria were found in areas with different distributions of the species. The occurrence of Alternaria spp. was studied by analyzing isolates from symptomatic potato leaves during multiyear sampling. In addition to Alternaria solani, we detected three more large-spored species identified as A. linariae (syn. A. tomatophila), A. protenta, and A. grandis that were involved in early blight disease on naturally infected potato leaves in Serbia. Differentiation of species was supported by phylogeny obtained from the DNA sequences of the GAPDH, calmodulin and Rpb2 genes. Our findings present a new perspective into the population structure of large-spored Alternaria species associated with early blight disease. Within the groups of large-spored Alternaria present in Serbia, evidence of A. protenta at high frequency reveals new insight into the contribution of Alternaria species in early blight disease. This work opens new perspectives for early blight management, while the distribution of different species on the same host suggests that the etiology of disease could depend on crop organization and the presence of other Alternaria hosts in close proximity to potato plants.